Sensing Properties Of WO3 /Pd Thin Films Deposited On Porous Silicon Substrates Using Pulsed Laser Deposition - Abed, Mayada A.; Mutlak, Falah A-H. (Iraqi Journal of Science, 2025)
The current research examines the distinct sensitivity displayed by WO3/Pd films prepared using the Pulsed Laser Deposition (PLD technique using a porous silicon substrate (PS). Tungsten oxide impregnated with palladium (WO3/Pd) films are created for the purpose of sensing Nitrogen Dioxide (NO2) by employing PLD with different laser pulse energies of 600, 800, and 100 mJ). The ablation process utilizes a laser device that uses a Q-switched Nd:YAG crystal to produce high-intensity light pulses that are precisely 1064 nm in wavelength. A frequency of 1 Hz and a pulse duration of 10 ns characterise the laser system. It operates upon an n-type Si (111) substrate made of porous silicon. Field emission-scanning electron microscopy, photoluminescence spectroscopy, X-ray diffraction, and Raman scattering are used to examine the morphological features, optical structure, and crystal structure of the WO3/Pd NPs. When the pulse laser’s power grows, the WO3/Pd thin film has sharper peaks, suggesting a strengthening of the crystallinity. The size of the surface grains increased, and this prompted a corresponding increase in the energy gap. As a result, the level of homogeneity was enhanced. The study examines how Pd affects the rate at which nanoparticles of tungsten trioxide grow. A more sensitive response is observed when Pd was present, decrease the operating temperature of the nanoparticles, and keep the sensitivity high even when the temperature is room temperature.